Dynamism of Labour Union, Social Order and Good Governance in Nigeria - Kuforiji, Aramide Arinola; Oikhala, Gabriel Izokpu (Universitas Airlangga, 2025)
Abstract Nigerians have historically utilized the Nigeria Labour Congress (NLC) as a platform to challenge government policies, actions, and inactions, not only on behalf of the working class but for the broader Nigerian populace. Consequently, this study examines the collaborative efforts between Nigerian labour unions and the government in fostering social order and promoting good governance. A cross-sectional study was conducted in Nigeria's South West geopolitical zone, selected due to the region's history of industrial unrest. The research employed a quantitative methodology, utilizing a survey approach. A sample of 200 participants was drawn from the study area, with union leaders selected through purposive sampling. The selection criteria included willingness to engage, current employment status, active membership in recognized labour unions, and at least one year of involvement in union activities. The theoretical framework for this study is grounded in the concept of Governance and Social Order, which posits that societies are composed of various economic, political, cultural, religious, and professional groups. The operations of these groups are typically regulated by an institutionalized system involving the legislative, executive, and judicial branches. According to the survey, 95% of respondents believed that labour union members should participate in the policy-making process within their respective sectors. Furthermore, the study highlighted strong support for collaboration between labour unions and the government, with respondents indicating that such cooperation would enhance accountability, governance, and public trust in government activities. These findings significantly contribute to academic discussions surrounding government policy formulation and implementation. Keywords: labour union; social order; social stability; governance; good governance. Abstrak Secara historis, masyarakat Nigeria telah memanfaatkan Kongres Buruh Nigeria (NLC) sebagai platform untuk mempertanyakan kebijakan, tindakan, dan kelalaian pemerintah, tidak hanya untuk kelas pekerja, tetapi juga untuk seluruh masyarakat Nigeria. Oleh karena itu, penelitian ini menganalisis upaya kolaboratif antara serikat pekerja Nigeria dan pemerintah dalam membangun tatanan sosial dan mempromosikan pemerintahan yang baik. Penelitian ini dilakukan dengan menggunakan pendekatan cross-sectional di zona geopolitik Nigeria bagian Barat Daya, yang dipilih karena sejarah ketegangan industri di wilayah tersebut. Metodologi yang digunakan dalam penelitian ini adalah kuantitatif dengan pendekatan survei. Sampel terdiri dari 200 peserta yang dipilih melalui teknik purposive sampling, dengan memilih pemimpin serikat pekerja sebagai responden. Kriteria pemilihan mencakup kesiapan untuk berpartisipasi, status pekerjaan saat ini, keanggotaan aktif dalam serikat pekerja yang diakui, dan keterlibatan setidaknya selama satu tahun dalam kegiatan serikat. Kerangka teori dalam penelitian ini berlandaskan pada konsep Tata Kelola dan Tatanan Sosial, yang mengemukakan bahwa masyarakat terdiri dari berbagai kelompok ekonomi, politik, budaya, agama, dan profesi. Operasional kelompok-kelompok ini biasanya diatur oleh sistem yang terinstitusionalisasi yang mencakup cabang legislatif, eksekutif, dan yudikatif. Berdasarkan hasil survei, 95% responden berpendapat bahwa anggota serikat pekerja seharusnya dilibatkan dalam proses pembuatan kebijakan di sektor masing-masing. Lebih lanjut, penelitian ini menunjukkan dukungan kuat terhadap kolaborasi antara serikat pekerja dan pemerintah, dengan responden menunjukkan bahwa kerja sama semacam itu dapat meningkatkan akuntabilitas, tata kelola, dan kepercayaan publik terhadap kegiatan pemerintah. Temuan ini memberikan kontribusi signifikan terhadap diskursus akademis mengenai perumusan dan pelaksanaan kebijakan pemerintah. Kata kunci: serikat pekerja; tatanan sosial; stabilisasi sosial; tata kelola; tata kelola yang baik.